Emaranhamento e propriedades críticas em cadeias de spin exatamente solúveis - Almeida, Dalson Eloy (2013)
In this work, we investigate the one-dimensional XY model, as well as an exactly solvable two-leg spin ladder with three-spin interactions. We obtain analytically the nite-size corrections of the low-lying energies and determine the central charge as well as the scaling dimensions. By using the correlation matrix method, we also study the nite-size corrections of the Rényi entropy of the ground state and of the excited states. Our results are in agreement with the predictions of the conformal eld theory. Last but not least, in the appendix (Apêndice A), we summarize the main steps of the diagonalization of the general biquadratic hamiltonians in term of Fermi operators, and thereafter, we also discuss the correlation matrix method to calculate the Rényi entropy.